SMARTLY: Smart Trolley Based on Augmented Reality as a Solution for Shopping Issues in Supermarkets - Putri Ridha; Putri Ridha Maulia Nazariah; Meta Nydia Putri; Nur Aini Alhamda; Risti Febrianti; Aulia Zikri Rahman (Journal of Logistics and Supply Chain, 2023)
Indonesian society has a high interest in shopping at supermarkets. However, there are still several issues when shopping at supermarkets, such as long queues at cashier counters, discrepancies in consumer budgets, and difficulties in finding desired product locations. Therefore, there is a need for a tool that can help enhance the effectiveness of shopping activities in supermarkets, and one such solution is the creation of the SMARTLY tool. SMARTLY is a new innovation that will be applied to trolleys with a smart system based on Augmented Reality (AR). The method used in writing this article is a planned experimental method that starts with literature review, product design, prototype creation, testing, troubleshooting, and evaluation. Based on research findings, SMARTLY can provide information about product locations, prices, names, promotional quantities, and specifications, encompassing various details about the products to be purchased. Thus, this tool can act as a solution to all the problems mentioned earlier.